PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN SEMANGAT PADA PESERTA DIDIK DI SMP IT INSAN PERMATA MALANG - Lutfia Khummayroh; Anwar Sa’dullah; Bahroin Budiya (VICRATINA, 2022)
The role of education in life is very important to form a good human personality.Islamic religious education has a very important goal, namely to increase the faith,understanding, appreciation and experience of students about the religion of Islam sothat they become Muslims who believe and are devoted to Allah SWT and have noblecharacter in personal, community, nation and state life. Teachers are tasked witheducating, teaching, training their students and shaping students to become usefulpeople for their families, communities and countries.The spirit of a person to carry outworship is what makes him closer to Allah SWT. In this case, it can be seen that today'sconditions are messy, especially at the age of teenagers who have differentenvironments and most importantly the environment that affects today's children,namely the living environment, namely the family and the place of children'seducation, many children have environmental factors. a family lacking in religion.Therefore, SMP IT Insan Permata Malang is a Qur'ani school with an Islamic character,which has the aim of making students have Qur'anic characters because at this schoolthey have a different phenomenon, they have worship activities which are very rarelyowned by schools. Such as prayer, dhikr and other worship activities.